علاقة تخطيط الموارد البشرية بالتخطيط الاستراتيجي وأثره في المنظمات بالتطبيق على شركة النسيم الليبية للصناعات الغذائية - عبد السلام سالم عبدالله; عياد المخزوم الواعر; علي المبروك النائض; إبراهيم مسعود احمد; جمال عبدالقادر سعد (Surman Journal of Science and Technology, 2024)
This study was conducted on Al- Naseem Company in Libya, a leading food industry company in the Libyan market, as a model for companies operating in developing countries. The study concluded that there is alignment between strategic planning and human resource planning at Al- Naseem Company, which has positively impacted employee performance and company profitability. The findings highlight the importance of integrated strategic planning with human resource plans to achieve corporate goals in a challenging environment like the Libyan market. Additionally, the study emphasizes that continuous changes in the business field, including globalization, local and international competition, and the influence of modern technologies (such as information technology), necessitate companies to reconsider their organizational structures, enhance collaboration between senior and lower management, and move away from centralization and bureaucratic procedures. The study recommends the necessity of developing clear human resource plans and strategies derived from the company’s comprehensive strategic planning, focusing on training programs to improve employee efficiency and effectiveness while reducing fixed and variable costs. Furthermore, it stresses the importance of having a clear future vision that strengthens the company’s competitive power and directs its human resource strategies toward achieving success in a highly competitive environment.